Dampak Fashion Halal terhadap Industri Tekstil Tradisional di Negara-Negara Mayoritas Muslim - Saepudin, Asep Bayu Saepudin (UIR Press, 2024)
This study investigates the impact of halal regulations and certification on the competitivenessof the traditional textile industry in Muslim-majority countries. Utilizing a qualitativedescriptive approach, data were collected through literature review, analyzing various relevantsources from the last decade. The findings reveal that while halal certification enhancesconsumer trust and opens new market opportunities, it also presents significant challenges fortraditional textile producers due to increased production and administrative costs. Moreover,the harmonization of halal standards at the international level remains a critical issue thataffects trade. This research contributes by providing a comprehensive analysis of the effects ofhalal regulations on product quality, innovation, production efficiency, and competitiveness.The study offers practical recommendations for policymakers and industry stakeholders toimprove the competitiveness of traditional textile products in an increasingly competitive globalmarket.